Developing Canva-Based Sitekol on Collage Topic for First-Grade Public Elementary School Students - Septiani, Alsa Ayu; Setiawan, Deni (Journal of Integrated Elementary Education, 2024)
The study aims to create a learning media product using Canva for elementary school students to alleviate the lack of learning materials, which has been negatively impacting student academic performance. The research also seeks to evaluate the practicality and effectiveness of the learning media product. This study uses research and development with ADDIE design. The results of the analysis revealed that some students do not meet the minimum standards and require learning tools to improve their skills in cutting and sticking when studying collage topics. This research developed Sitekol media on collage topics in the design stage using Canva and Wordwall applications. The validity test results showed that Sitekol media received a 90% score from media experts for color appearance, image combinations, fonts, media layout, videos, and practical use. Material experts rated it at 95.3% for material aspects, levels of thinking, and supporting learning content. Students also found Canva-based Sitekol learning media to be beneficial as a teaching tool due to its accessibility, portability, convenience, interactive features, and detailed learning media instructions. The statistical tests conducted resulted in significant findings with high average values. Students responded very positively to the practicality of the media, giving an average score of 4.9 out of 5, indicating 98% of the ideal score. It can be concluded that using Canva-based Sitecol learning on grade 1 collage material exhibits practicality and validity as a learning medium.